A seed-less method for synthesis of ultra-thin gold nanosheets by using a deep eutectic solvent and gum arabic and their electrocatalytic application. Issue 41 (7th May 2015) - Tohidi, Maryam; Mahyari, Farzaneh Aghakhani; Safavi, Afsaneh
<x xml:space="preserve">Abstract</x> Ultra-thin and large gold nanosheets were easily synthesized by using a deep eutectic solvent as a reducing and directing agent with gum arabic as a stabilizer and shape-controlling agent through a seed-less protocol.